Superficial venous patterns of the cubital fossa among volunteers from Hospital Kuala Lumpur - A/L Ramasamy, Saravanan (2012)
Introduction Cubital fossa is a space in anterior to the elbow which contains important vessels and nerves in the arm. Superficial veins of cubital fossa are commonly used for blood sampling, transfusions and for intravenous injections often under conditions of emergency. These veins are useful in arteriovenous fistula creation for hemodialysis. Besides that, they are used for creation of forearm flaps in plastic surgery. The arrangement of the superficial veins in the cubital fossa however is subjected to considerable variation. Different patterns of superficial cubital veins and their percentages of occurrence have been reported in various races. This prospective study among Malaysians from three races (Malays, Chinese and Indians) was planned since the superficial veins in the cubital fossa are important clinically and their arrangements are subject to racial variation. Objectives The aim of the study is to observe and describe the distribution of anatomical variations of the superficial veins of the cubital fossa among Malay, Chinese and Indian volunteers from Hospital Kuala Lumpur. Methodology and Study Design The study is designed as a descriptive cross-sectional survey involving a simple examination of the superficial veins of cubital fossa among volunteers from Hospital Kuala Lumpur. My sample is composed of three hundred volunteers from three major ethnicities Malays, Chinese and Indians aged from eighteen and above. I, myself performed the duplex ultrasound assessment with the guidance from my supervisors in the vascular unit HKL. The patterns of the veins were drawn onto a survey form. Results Based on my analysis, the commonest type of anastomosis seen was type 1 in both genders with female having 33.3% and male having 34.0% on the right cubital fossa and 32.0% in female and 34.0% in male on the left cubital fossa. Type 1 was the commonest among Malays and Indians. It was 40.0% and 37.0% of right and left cubital fossa in Malays. Indians meanwhile had 36.0% and 41.0% on the right and left cubital fossa. While in Chinese type 3 of anastomosis observed the most. It was 38.0% and 40.0% on right and left cubital fossa. The mixed type combination on both right and left cubital fossa was the highest prevalence in all 3 major ethnicities. There was no significant difference between gender and patterns but there was a significant difference in between ethnicities and patterns of cubital fossa. Conclusion Superficial veins of cubital fossa have their clinical importance. The understanding of patterns in genders, ethnicities and combination patterns of both cubital fossas will assist in clinical procedures. Duplex ultrasound has provided a great understanding of the anatomy of superficial veins of cubital fossa.